The power of forward guidance in a quantitative TANK model - Rafael Gerke; Sebastian Giesen; F. Alexander Scheer (Deutsche Bundesbank, 2020)
We quantify the macroeconomic effects of interest rate forward guidance in an estimated medium-scale two-agent New Keynesian (TANK) model. In general, such models can dampen or amplify the power of forward guidance compared to a representative agent model. Our empirical estimates indicate a dampening, as there is sufficient countercyclical redistribution.An interaction with asset purchases gives rise to non-linear effects that depend on the horizon of forward guidance.
Keywords: E44; E52; E62; 330; Forward Guidance; Hand-to-mouth households; Redistribution; Bayesian Estimation; Asset purchase program